Karakteristik dan Identifikasi Senyawa Ekstrak Etanol Daun Pacing Tawar (Costus speciosus) - Putri Jihannisa; Wury Damayantie; Murtiyana Sari (Lembaga Pengembangan Kinerja Dosen, 2025)
The wild ginger leaves (Costus speciosus) is used by the community as a traditional medicine, with its rhizome being utilized as an antipyretic, diuretic and anti-inflammatory agent. This plant contains secondary metabolite compounds such as alkaloids, flavonoids, polyphenols, quinones, tannins and saponins. This research aims to identify saponin compounds and characterize the moisture content and ash content in the ethanol extract of the white costus (Costus speciosus) leaves. The white costus leaves sample was extracted using the maceration method with 96% ethanol as the solvent. The extraction yielded a rendemen value of 13.3%. Non-specific characterization tests included moisture content and ash content. The results for the moisture content of the white costus leaf simplicia were 3.3%, which meets the quality requirement of not more than 10% according to Regulation of the Food and Drug Supervisory Agency Number 32 of 2019. The ash content test result for the simplicia was 0.97%, which also meets the standard requirement of the Indonesian Herbal Pharmacopoeia, which is less than 10.7%. Phytochemical screening was conducted to identify the types of compounds contained in the extract. Based on the phytochemical screening results, the 96% ethanol extract of white costus leaves positively contains alkaloids, tannins, saponins, and steroids.